Ectopic pancreatic tissue in the wall of the small intestine: Two rare case reports. Issue 35 (September 2017) - Li, Jiannan; Huang, Haibin; Huo, Sibo; Liu, Ying; Xu, Guangmeng; Gao, Hongwen; Zhang, Kai; Liu, Tongjun
Abstract: Rationale: Ectopic pancreas, which is a kind of rare congenital disease, forms during embryonic development. It can occur throughout the whole gastrointestinal tract, but has a low tendency to develop in the wall of the small intestine. It is easy for patients with ectopic pancreases to be misdiagnosed because the symptoms are untypical and can vary. Patient concerns: In the present study, we reported two rare cases of ectopic pancreatic tissue in the wall of the small intestine, which presented with obvious abdominal pain and distention. Diagnosis: The laboratory tests and computed tomography (CT) scans didn't reveal any evidence of ectopic pancreas. Interventions: The two patients received small intestine masses resection and intestinal anastomosis. Outcomes: During surgery, an intestinal mass with a diameter of 4.0 cm was found in the first patient. An intestinal mass with a diameter of 0.8 cm, jejunum perforation, and diffuse peritonitis were found in the second patient. Histological analyses of the dissected intestinal masses confirmed them as ectopic pancreatic tissue. Interestingly, for the second patient, the intestinal perforation and diffuse peritonitis were not induced by the ectopic pancreas, but by a jujube pit that was found in the perforated site of the intestine. Lessons: Our study demonstrated that an ectopic pancreas should be considered in cases of untypical abdominal symptoms with intestinal masses.